2015
DOI: 10.2298/sarh1510520l
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasomotor reactivity and apnea test in symptomatic and asymptomatic high-grade carotid stenosis

Abstract: Introduction. Cerebral vasomotor reactivity (VMR) represents an autoregulatory response of the arterial trunks on the specific vasoactive stimuli, most commonly CO2. Objective. The aim of this retrospective study was to compare VMR in high-grade symptomatic (SCAS) and asymptomatic carotid stenosis (ACAS), using the apnea test to evaluate the hemodynamic status. Methods. The study included 50 patients who were hospitalized at the neurology and vascular surgery departments as part of preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The primary objective of this study was to investigate the impact of CAS on cerebral hemodynamics and autoregulation in both symptomatic and asymptomatic patients. Our results demonstrated that CAS was associated with impaired cerebral vascular reactivity, corroborating previous findings [ 88 – 90 ]. Notably, a larger proportion of symptomatic CAS patients exhibited incomplete CoW anatomy, which potentially contributed to their more severe clinical presentation.…”
Section: Discussionsupporting
confidence: 93%
“…The primary objective of this study was to investigate the impact of CAS on cerebral hemodynamics and autoregulation in both symptomatic and asymptomatic patients. Our results demonstrated that CAS was associated with impaired cerebral vascular reactivity, corroborating previous findings [ 88 – 90 ]. Notably, a larger proportion of symptomatic CAS patients exhibited incomplete CoW anatomy, which potentially contributed to their more severe clinical presentation.…”
Section: Discussionsupporting
confidence: 93%
“…Evaluation of VMR before and after carotid endarterectomy (CEA) is significant because of the evaluation of the revascularization effect on cerebral hemodynamics, as well as the increasingly important choice of the right time to perform it. The CEA contributes to the normalization of collateral circulation and restitution of cerebral hemodynamics in symptomatic [47,48,[52][53][54][55][56] and asymptomatic carotid disease [57][58][59][60][61]. Reduced VMR may encourage consideration of CEA or stenting in asymptomatic carotid disease or extra/intracranial bypass surgery in patients with recurrent hemodynamic stroke or TIA [3,4,52,62].…”
Section: Transcranial Doppler In Reduced Vasomotor Reactivitymentioning
confidence: 99%
“…To our knowledge, there are no studies assessing VMR in early carotid disease, which is why the correlation between IMT and VMR is not investigated enough. Even though most of the studies focus on advanced or clinically significant carotid stenosis or even carotid occlusion and its correlation with VMR, it is only logical to assume that increased IMT as a marker of early atherosclerotic changes would correlate with small cerebral vessel function and VMR itself as they are both subjected to the same process, i.e., atherosclerosis [12,21,27]. Our study shows the possibility of this correlation, implicating that in patients with normal IMT, VMR is preserved.…”
Section: Discussionmentioning
confidence: 58%